Implementasi Budaya dan Iklim Organisasi di MIN 1 Medan Sumatera Utara - Abdullah Fikri Sholehuddin SN; Siti Aisyah; Rabbirham; Mesiono; Toni Nasution (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to explore: First, explore the organizational culture that occurs at MIN 1 Medan. Second, explore the characteristics of organizational culture that occur at MIN 1 Medan. Third, explore the development of the organizational climate that occurred at MIN 1 Medan. This research method is a qualitative type with a descriptive approach. The instruments used in this research were observation, interviews and documentation studies. The location of this research is MIN 1 Medan, North Sumatra. This research data analysis uses three steps, data reduction, data presentation and conclusion drawing. The results of the research show that: First, the organizational culture that occurs at MIN 1 Medan is the teaching and learning process, both teachers and students understand how it works, namely by helping each other, the leadership, namely the principal, teachers and staff work together in building the MIN School. 1 Medan will be even better in the future and the school management is relatively good between the Principal, Teachers, Staff and Students of MIN 1 Medan as well as the school culture. Second, the characteristics of organizational culture that occur at MIN 1 Medan, namely 1. Norms; Organizational culture in schools is also characterized by the existence of norms that contain standards of behavior for school members, both for students and teachers. 2. Philosophy; namely, the existence of policies relating to the organization's beliefs in treating school members. Organizational culture is characterized by the belief of all members of the organization in seeing things in an essential way. 3. Rules; namely the existence of strict guidelines, linked to the progress of the organization. Third, the development of the organizational climate that occurs at MIN 1 Medan, namely a) First, the implementation of the main character and mission of education as well as the promotion of basic moral values ​​in students. b) Second, the involvement and commitment of the school community (teachers, students and parents) in their work. c) Third, preventing violence and conflict in schools. d) Fourth, prohibition of verbal and psychological violence. e) Fifth, the principal and teachers treat students fairly, equally and with respect.